Health-related quality of life in patients with RAS wild-type metastatic colorectal cancer treated with panitumumab-based first-line treatment strategy: A pre-specified secondary analysis of the Valentino study. (August 2020) - Raimondi, Alessandra; Di Maio, Massimo; Morano, Federica; Corallo, Salvatore; Lonardi, Sara; Antoniotti, Carlotta; Rimassa, Lorenza; Sartore-Bianchi, Andrea; Tampellini, Marco; Ritorto, Giuliana; Murialdo, Roberto; Clavarezza, Matteo; et al.
Abstract: Background: Quality of life (QoL) patient-reported outcomes (PROs) data from pivotal first-line trials in metastatic colorectal cancer (mCRC) are poor. The Valentino study showed that de-escalation to single-agent panitumumab after 4-month induction with panitumumab-FOLFOX is inferior to panitumumab-5-FU/LV in patients with RAS wild-type mCRC, although slightly reducing toxicity. We report QoL, a secondary end-point. Methods: PROs were assessed by European Organisation for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire – Core 30 (QLQ-C30), EORTC QLQ-CR29, EuroQol EQ-5D questionnaires, at baseline and every 8 weeks until disease progression. First two evaluations correspond to induction treatment (identical in both arms), while subsequent to maintenance. To describe QoL changes over time, mean changes from baseline at each time point were calculated in overall population. To compare maintenance between two arms, mean changes and proportion of improved/stable/worse patients versus baseline were compared for each item. Results: In arm A/B, 91.5%/92.0% of enrolled patients completed questionnaires at baseline. No significant differences in the two arms were reported in compliance, baseline scores and mean changes versus baseline for the three questionnaires during maintenance (24/32/40 weeks). Overall, mean changes versus baseline showed an early deterioration during induction with partial recovering during maintenance for global QoL, functional scales and several symptoms/items of QLQ-C30 (fatigue, nausea/vomiting, appetite loss, diarrhoea) and QLQ-CR29 (body image, dry mouth, hair loss, taste, faecal incontinence, sore skin), and EQ-5D Visual Analogue Scale (VAS) score. Conclusion: In patients with RAS wild-type mCRC, induction with oxaliplatin-containing chemotherapy plus anti-EGFRs induces a transient significant QoL deterioration. After induction phase, treatment deintensification determines an overall recovery of health-related QoL, besides the expected prevention of oxaliplatin-related neurotoxicity. Highlights: This study reports on a pre-specified secondary analysis of the randomized open-label phase II Valentino trial. Quality of Life (QoL) changes are reported through patient-reported outcomes. Patients affected by RAS wild type metastatic colorectal cancer were treated in first-line with panitumumab (pan) plus/minus fluorouracil/leucovorin maintenance after FOLFOX-pan induction. The results of this study showed an early deterioration of QoL during induction with partial recovery during maintenance. No significant QoL differences between the two maintenance treatment arms are reported.